Storm front [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Montana rescue, 2018)
"A tornado has destroyed a small Minnesota community and among the missing are not only a group of students but PEAK Rescue team leader Chet King. Ty Remington will stop at nothing to rescue his mentor, not even when the girl he loved--and lost--walks back into his life"--